ANALYSIS OF THE HUMAN FACTOR AT CONTROL OF THE MODERN AIRCRAFT - Павлова, С.В.; Благая, Л.В. (Proceedings of National Aviation University, 2012)
Functional interaction features of the operator with a difficult control system have been considered at airplane control. Necessity of working out of vector model of the operator as integral part of difficult system has been revealed.